A Coronary Artery Perforation: Successful Complication Management after Intravascular Ultrasound Imaging Guided Covered Stent Implantation - Zebrauskaite, Aiste; Ziubryte, Greta; Medzevicius, Petras; Morkunaite, Kristina; Unikas, Ramunas; Jarusevicius, Gediminas (Archives of Clinical and Medical Case Reports, 2022)
A coronary artery perforation is a rare, but dangerous periprocedural complication. In this case the perforation stented with two covered stents, balloon inflations applied. Despite the treatment extravasation persisted. Intravascular ultrasound (IVUS) imaging identified the reasons of persisting extravasation. IVUS guided third covered stent implantation leaded to the successful treatment.